Retinopathy of prematurity: Postnatal weight gain and risk factors profile; a hospital-based study from a tertiary care center - Subramanya, Pooja; Pradeep, G C M; Sharanabasavesh, M; Krithika, M V (Indian Journal of Child Health, 2021)
Background: Premature infants often develop blindness in one or both eyes due to disparity in retinal growth. This condition is termed as retinopathy of prematurity (ROP). Aim: The aim of the study is to study the postnatal weight gain pattern of preterm infants (Age < 32 weeks) and risk factors of ROP in a tertiary care center and to validate the lower birth weight and gestational age (GA) for ROP. Methods: Hospital-based study on 110 preterm neonates admitted in the neonatal intensive care unit (NICU) who fulfilled the criteria for ROP screening. On screening, 55 neonates were identified to have ROP and 55 neonates identified to have no ROP. The profiles of ROP and risk factors were documented according to the International Classification for ROP recommendations. The data were analyzed for GA, birth weight, and risk factors predisposing to ROP. Results: A total of 110 preterm neonates were screened, out of which, 55 had ROP. The mean GA (P = 0.002), Apnea (P = 0.001), ventilation (P = 0.001), and surfactant (P = 0.001) were observed a significant difference. Further, a significant difference in weight gain pattern in the two groups (P < 0.05) was also observed. The group without ROP had a better weight gain pattern than the group with ROP. Conclusion: Our study revealed prematurity, low birth weight, and birth weight increasing patterns were found to be strong predictors of ROP. GA, apnea, ventilation, and surfactant were found to be statistically significant factors associated with ROP.